2002
DOI: 10.1210/jc.87.8.3876
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Activity of 25-Hydroxyvitamin D-1 -Hydroxylase Are Restricted in Cultures of Human Syncytiotrophoblast Cells from Preeclamptic Pregnancies

Abstract: The human placenta synthesizes 1,25-dihydroxyvitamin D(3) and expresses the vitamin D receptor. Because preeclampsia (PE) is associated with low circulating levels of maternal 1,25-dihydroxyvitamin D(3) and IGF-I, it is possible that alterations in calcium metabolism seen in PE could occur at the level of the fetoplacental unit. In this study, the patterns of gene expression and enzyme activity of 25-hydroxyvitamin D-1 alpha-hydroxylase (1 alpha-hydroxylase) and the abundance of IGF-I mRNA in placentas from no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 0 publications
3
74
0
1
Order By: Relevance
“…Altered mRNA expressions for CYP27B1, CYP24A1, or VDR were previously reported to be either increased or decreased in preeclamptic placentas compared with normal placentas (11,13). In our study, we determined the distributions and expressions of major vitamin D metabolic components, including VDBP, CYP2R1, CYP27B1, CYP24A1, and VDR, by immunostaining and by Western blot analysis in placental tissues from normal and preeclamptic pregnancies.…”
Section: Discussionmentioning
confidence: 97%
“…Altered mRNA expressions for CYP27B1, CYP24A1, or VDR were previously reported to be either increased or decreased in preeclamptic placentas compared with normal placentas (11,13). In our study, we determined the distributions and expressions of major vitamin D metabolic components, including VDBP, CYP2R1, CYP27B1, CYP24A1, and VDR, by immunostaining and by Western blot analysis in placental tissues from normal and preeclamptic pregnancies.…”
Section: Discussionmentioning
confidence: 97%
“…Cytotrophoblasts were isolated and cultured as described (18,19). Villous tissue was enzymatically dispersed; cytotrophoblasts were separated on a Percoll gradient, plated in DMEM-HG with 20% fetal bovine serum (FBS) and incubated at 37jC (95% humidity and 5% CO 2 atmosphere).…”
Section: Methodsmentioning
confidence: 99%
“…Another study found that serum levels of the fat-soluble vitamins A, D, and E were each lower in preeclamptic women compared with normotensive pregnant and nonpregnant controls (485), which raises the possibility that confounding from overweight, obesity, and poor nutrition may explain why the levels of several fatsoluble vitamins were all lowered in preeclamptic women. A placental abnormality has been hypothesized to explain lower calcitriol levels in preeclampsia, with conflicting results obtained showing decreased (248) and increased (286) placental expression of Cyp27b1. However, since the placenta contributes very little calcitriol to the circulation of pregnant women (see sect.…”
Section: Human Datamentioning
confidence: 99%